(untitled) (The International Journal for Scientific Research, 2023)
In light of the Kingdom’s Vision 2030, we believe that it is necessary to analyze the information crime system and the electronic transactions system to determine the correct legal adaptation of digital crime and the applicable law. The spread of technology and the expansion of the circle of digital crimes and their exit from the scope of the threat to the stage of reality, which has become a concern for many, and threatens countries and societies from the economic and social aspects, as well as the emergence of frequent and increasing technological development in all the circles that surround us, have made it a tool for committing many crimes with technology. High rates that violate freedoms, steal a lot of money, and destabilize the stability and security that prevailed in previous eras, before the spread and development of technology and its increasing impact on all areas of our Arab society in particular, and in the world as a whole. The Saudi regulator has addressed the criminalization and punishment of all criminal forms of digital crime, explaining its dimensions and consequences under a special law on information crimes. It has also allocated penalties for contributors, and even considered the contributor to the digital crime to be an original perpetrator. It also concluded many rules, in addition to the penal rules in Saudi law, which must be strictly affected by the legal person in the event that he commits digital crimes, in addition to punishing the ordinary person representing the legal person and not being satisfied with imposing penalties on the legal person only. It is also necessary to take into account the seriousness of the person instigating the digital crime, as he is an original perpetrator who deserves the full original punishment. Moreover, the instigator may be from outside the country that is the subject of the digital crime.